PENERAPAN CORPORATE SOCIAL RESPONSIBILITY DALAM PENGELOLAAN WAKAF PRODUKTIF - Masruchin (Istithmar: Jurnal Studi Ekonomi Syariah, 2019)
Corporate Social Responsibilityis a concept that a company has various forms of responsibility to all stakeholders including consumers, employees, shareholders, communities and the environment in all aspects of the company's operations that include economic, social, and environmental aspects. Therefore CSR is closely related to "sustainable development", in which a company, in carrying out its activities must base its decisions not only on the impact on economic aspects, such as the level of profits or dividends (profits), but also must consider the social and environmental impacts that arise from that decision, both for the short term and the longer term.Pondok Modern Darussalam Gontor (PMDG), in managing its Productive Waqf by establishing business units which mostly involve workers from the local society around PMDG. They are employed according to their skills. This is a form of implementing CSR in order to help advance and improve the welfare of the local society. The existence of these various business units is one of the educational facilities and as a form of CSR application which is actually intended to educate in the fields of independence, entrepreneurship, sincerity and sacrifice.PMDG involvement in social activities that are useful for the local society such as infrastructure development and village facilities, regeneration of students who are from around PMDG to be able to get higher education with funding from the PMDG, doing guidance to the local society through various religious activities, educational and economic activities is a form of PMDG responsibility to the local society environment and also to all stakeholders such as students, Ustadz, employees, so as to provide social and environmental impacts for the short term and the longer term.